Superior Gas Sensing Properties of Monolayer PtSe2. Issue 5 (14th December 2016) - Sajjad, Muhammad; Montes, Enrique; Singh, Nirpendra; Schwingenschlögl, Udo
Abstract : First‐principles calculations of the structural and electronic properties of monolayer 1T‐PtSe2 with adsorbed (a) NO2, (b) NO, (c) NH3, (d) H2 O, (e) CO2, and (f) CO molecules are discussed. The results point to great potential of the material in gas sensor applications. Superior sensitivity is demonstrated by transport calculations using the nonequilibrium Green's function method.